Involvement of Heme in Colony Spreading of Staphylococcus aureus - Liu, Chao-Chin; Lin, Mei-Hui (Frontiers in Microbiology, 2020)
Staphylococcus aureus spreads rapidly on the surface of soft agar medium. The spreading depends on the synthesis of biosurfactants, i.e. phenol soluble modulins (PSMs), which facilitate colony spreading of S. aureus. Our earlier study demonstrated that water accumulates in a colony is important to modulate colony spreading of S. aureus. The current study screened a transposon-based mutant library of S. aureus HG001 and obtained four non-spreading mutants with mutations in hemY and ctaA, which are involved in heme synthesis. The spreading ability of these mutants was restored when the mutants are transformed with a plasmid encoding hemY or ctaA, respectively. HemY mutants, which do not synthesize heme B, were able to spread on agar medium supplemented with hemin, a heme B derivative. By contrast, hemin supplementation did not rescue the spreading of the ctaA mutant, which lacks heme B and heme A, indicating that heme A is also critical for colony spreading. Moreover, mutations in hemY and ctaA had little effect on PSMs production but affect ATP production and water accumulation in the colony. In conclusion, this study sheds light on the role of heme synthesis and energy production in the regulation of S. aureus colony spreading, which is important for understanding the movement mechanisms of bacteria lacking a motor apparatus.